Romanticization or Reality: It Ends with Us by Colleen Hoover Through Corpus Stylistics Perspective - Kaonedy, Jesselyn; Istiqomah; Sastia, May; Nasution, Diantry Binarwaty Habibie; Rangkuti, Rahmadsyah (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2025)
Corpus stylistics, which involves the analysis of electronic archives of written material, facilitates the understanding of connections between words. This research aims to provide linguistic evidence regarding the genre of Colleen Hoover's popular fiction, It Ends with Us, specifically, to ascertain whether it is a pure romance novel or incorporates aspects of literary realism. A descriptive qualitative approach, grounded in Mahlberg's (2013) corpus stylistics theory, is employed. The primary data for analysis are the four most frequently occurring verbs identified using AntConc. The collocations associated with each verb are subsequently categorized into "attempts to romanticize" or "narrations of reality" to determine the prevailing stylistic strategy. The research demonstrates that the novel utilizes a greater proportion of "realistic" words compared to "romantic" words, thereby indicating its alignment with literary realism. The narrative modifications are intended to heighten the story's engagement, rather than to romanticize domestic abuse or toxic relationships.